Reading and writing in medieval England : essays in honor of Mary C. Erler - Chase, Martin; Kowaleski, Maryanne; Erler, Mary Carpenter (The Boydell Press, 2019)
Reading, writing, sharing texts, and book ownership in the fifteenth and sixteenth centuries, and how they fostered social and intellectual links and networks between individuals, particularly among women: these are subjects which the pioneering work of Mary C. Erler has done so much to illuminate. The essays here, in this volume in her honour, build on her scholarship, engaging with Professor Erler's characteristic use of bibliography in the service of biography by investigating how the physical object of the book can enlighten our understanding of medieval readers and writers. They analyze, for example, what "reading" means in terms of the act itself (and the accessories, such as bookmarks, that helped to set the stage for reading), whether done aloud or silently, in such different venues as an aristocratic court, bourgeois household, village community, and monastic cloister. They also consider the culture of medieval reading practices, especially those of women, across social classes, and in terms of the transition between the pre- and post-Reformation periods; the fluidity of genre boundaries; and changes in devotional reading and writing in this liminal period. A wide variety of genres are covered, including secular romance, devotional texts, schoolbooks, and the illustrated Old Testament preface to the famous Queen Mary Psalter, which recasts the story and image of ancient Israelites to suit elite readerly taste